A Symptomatic Killian-Jamieson Diverticulum Detected by Ultrasonography. Issue 2 (30th December 2015) - Navez, M.; Bosschaert, P.; Degols, J. C.
Killian-Jamieson diverticulum (KJD) is a rare entity resulting from the mucosal herniation through a lateral area of weakness known as the Killian-Jamieson space below the cricopharyngeal muscle. Ultrasonographic diagnosis is exceptional. Moreover, symptoms are found in only eleven percent of patients. KJD in its symptomatic form must be correctly identified because its therapeutic management is in some points different of Zenker's diverticulum.